An axiomatization of the Nash bargaining solution - Geoffroy de Clippel (Brown University, Department of Economics, 2004)
I prove that the Nash bargaining solution is the only solution to satisfy `Disagreement Point Convexity' and `Midpoint Domination'. I explain how this improves previous results obtained by Chun (1990) and by Dagan et al. (2002).
Keywords: 330; Verhandlungstheorie